Taufik Abdullah: Historiografi Islam Indonesia Modern - Maknun, Lu'lu'il; Mansurnoor, Iik Arifin; Ardiansyah, Riki (Asshiddiqiyah Press and Publisher, 2025)
Taufik Abdullah is a prominent modern historian in the development of Indonesian historiography. As an enthusiast of history, discussing Taufik Abdullah is an essential aspect. Similarly, any discourse on modern historiography is incomplete without reference to his works. This study examines the evolution of modern historiography and the role of Taufik Abdullah as presented in his book Islam dan Masyarakat: Pantulan Sejarah Indonesia (Islam and Society: Reflections on Indonesian History). The research method employed is library research, utilizing a qualitative approach as the research procedure to produce descriptive data in written form. The primary data for this study is Taufik Abdullah’s book Islam dan Masyarakat: Pantulan Sejarah Indonesia. Meanwhile, the secondary data includes other books authored by Taufik Abdullah and/or discussing his contributions, as well as literature that explores modern historiography. This research is expected to contribute to broadening insights and understanding of modern historiography and the historians involved in its development.